Desenvolvimento de um sistema computacional de apoio ao planejamento estratégico pessoal - Oliveira, Gláucia Londero de (2009)
This thesis presents a computational tool to aid the Strategic Personnel of Estrada. The Model of Strategic Personnel Planning of Estrada is composed of five areas of expertise or performance: individual planning, professional planning, family planning, business planning and personal social participation planning. The developed tool is simple to use, and can be accessed by who is doing the planning and who is helping the planning. The planning is always tied to a period, and should be reviewed periodically to keep in line with the desires of the person, so the system should also allow the same person to have different plans.